Cost-effectiveness of classroom-based cognitive behaviour therapy in reducing symptoms of depression in adolescents: a trial-based analysis - Anderson, Rob; Ukoumunne, Obioha C.; Sayal, Kapil; Phillips, Rhiannon; Taylor, John A.; Spears, Melissa; Araya, Ricardo; Lewis, Glyn; Montgomery, Alan A.; Stallard, Paul (Wiley, 2014)
Background